2011
DOI: 10.1111/j.1464-410x.2011.10402.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve sparing can preserve orgasmic function in most men after robotic‐assisted laparoscopic radical prostatectomy

Abstract: •  Age and nerve sparing influence recovery of orgasm and erectile function after RALP. •  Men ≤60 years old and those who undergo BNS are most likely to maintain normal sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 33 publications
8
45
0
1
Order By: Relevance
“…Previous data have reported rates of up to 19% of patients complaining of PO after RP (Table 2) [2024272830313334]. More recently, Frey et al [30] reported that 23 out of 256 patients treated with RP suffered from PO over the postoperative period.…”
Section: Prevalence Of Orgasmic Dysfunctions After Radical Prostatectomymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data have reported rates of up to 19% of patients complaining of PO after RP (Table 2) [2024272830313334]. More recently, Frey et al [30] reported that 23 out of 256 patients treated with RP suffered from PO over the postoperative period.…”
Section: Prevalence Of Orgasmic Dysfunctions After Radical Prostatectomymentioning
confidence: 99%
“…Although UI and EF impairment have been previously associated with orgasmic modifications after surgery [25293035], no data have suggested strong predictors for PO occurrence after RP; however, a significantly higher prevalence of PO after ORP than after RARP has been reported (9.5% vs. 11.6%; p=0.04) [31]. Similarly, in a series of 156 RARP cases, Tewari et al [34] reported that only 3.2% of patients complained of PO after treatment. Overall, these data seem to suggest that robotic surgery may have a protective effect in terms of the incidence of PO, possibly related to the more careful and precise dissection of the bladder neck during RARP than in the open approach [31].…”
Section: Prevalence Of Orgasmic Dysfunctions After Radical Prostatectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these limits, we cannot draw a firm conclusion on the benefit of laparoscopic AAA repair on sexual function compared to open repair. In any case, judging from the results of robotic prostatectomy, 23 and considering the ability of the endoscope to magnify presacral nerves, laparoscopy may be advantageous in terms of postoperative sexual function, but this remains to be proven.…”
Section: Discussionmentioning
confidence: 98%
“…34 Nerve preservation improved the possibility of achieving orgasm postprostatectomy. These data are supported by our findings that show a decreased score for postoperative orgasmic function (IIEF-OF) in men with less nerve preservation and in those with more extensive nodal dissection.…”
mentioning
confidence: 97%